Awareness of the Risk of BRONJ/ARONJ Amongst Dental professionals in KPK - SHAHZAD, SUHAIL; Taran Kumar; Kanwal Ilyas; Muhammad TAriq (Khyber Journal of Medical Sciences, 2021)
Background:Osteonecrosis of the jaws is an established adverse side effect of nitrogen-containing bisphosphonates, also known as amino bisphosphonates. Since the first case reports in 2003, there has been an increased surge in the literature of osteonecrosis related to bisphosphonates. Despite the established risk, there is almost no evidence-based publications in Pakistan on awareness of GDPs regarding this complication. The aim of this study (the first of its kind), to investigate the degree of awareness of general dental practitioners treating patients receiving bisphosphonates/Antiresorptive Medications in the primary care sector of the possible risk of Bisphosphonate/Antiresorptives related osteonecrosis of the jaw (BRONJ/ARONJ). Methods:A questionnaire with a covering letter was sent to general dental practitioners working in private practices and Hospitals based work places in KPK. The questionnaire was designed to maintain total anonymity of the practitioners. Out of 200 GDPs requested in KPK 93 answered questionnaire were returned. Results:Participant’s response rate was 46.5%. 70% of respondents practiced in a mixed (Government hospitals + Private) setting. 100 % of respondents have come across the pharmaceutical term ‘Bisphosphonates’ or ‘Antiresorptive’ agents. 91/93 (98%) were also positive about being familiar with the indications for treatment with these agents. 92/93 were aware of a relationship between these agents and oral health. 50% were aware of current schemes/pathways/protocols which deal with patients on ‘Bisphosphonates’ seeking dental treatments.